LANGUAGE ACQUISITION AND LANGUAGE LEARNING ACCORDING TO THE BEHAVIORISM AND NATIVISM THEORY WHILE AL-QUR’AN PERSPECTIVE - Sarwadi, Sarwadi (Journal of Innovation Research and Knowledge, 2024)
Language acquisition and language learning is the nature of every human being, whether it’s done consciously or unconsciously because every human being communicates used oral and writing communication as directly and indirectly. Based on the covarative linguistic, various theories about language acquisition and laguage learning have emerged. This research method uses descriptive qualitative with a comparative approach. Meanwhile, the data in this research are the theories of nativism and behaviorism seen from the perspective of the Al-Qur'an. Based on the comparative analysis of the two theories seen from the perspective of the Al-Qur'an, it can be concluded that language acquisition and Language learning is carried out before the child is born, this can be seen from what have saide by the Allah "Allah has created humans according to nature, QS.al-Rum (30)". After that, humans are born into the world and gain understanding and have experience in language used, this is explained by Allah in the Al-Qur'an. Furthermore, behaviorist theory states that the influence of the environment to the children is very significant. The theory of behaviorism is explained in the Qur'an surah al-baqorah 31-33. "He taught Adam all the names (of objects), then presented them to the Angels and said: "Tell Me the names of these objects if you are indeed those who This is true. Thus, behavioral theory and nativism theory existed long before any research or evidence was carried out by experts.